Respuesta :
[tex] \frac{(x-1)(x+8)}{(x-6)(x+8)} = \frac{(x-1)}{(x-6)} [/tex]
The x-intercepts are where the graph crosses the x-axis, in other words what x is when y = 0. This is only when the numerator is zero. After simplifying and factoring out the (x+8), y = 0 only when x = 1.
* When x = 6 the denominator is zero and the function is undefined. x = 6 would then be a vertical asymptote.
The x-intercepts are where the graph crosses the x-axis, in other words what x is when y = 0. This is only when the numerator is zero. After simplifying and factoring out the (x+8), y = 0 only when x = 1.
* When x = 6 the denominator is zero and the function is undefined. x = 6 would then be a vertical asymptote.